Molecular detection of Hepatozoon canis and Babesia canis vogeli in domestic dogs from Cuiabá, Brazil - Spolidorio,Mariana Granziera (2011)
The objective of this study was to report for the first time infection by Hepatozoon spp. and Babesia spp. in 10 dogs from the city of Cuiabá, State of Mato Grosso, central-western Brazil. A pair of primers that amplifies a 574 bp fragment of the 18S rRNA of Hepatozoon spp., and a pair of primers that amplifies a 551 bp fragment of the gene 18S rRNA for Babesia spp. were used. Six dogs were positive for Babesia spp., and 9 were positive for Hepatozoon spp. Co-infection of Babesia spp. and Hepatozoon spp. was seen in 5 dogs. Sequenced samples revealed 100% identity with B. canis vogeli, and H. canis. This is the first molecular detection of H. canis in domestic dogs from Cuiabá. Additionally, it is described for the first time the presence of B. canis vogeli circulating among dogs in Cuiabá.